Pengembangan PLTMH dengan Model Multipowerhouse (MPH) untuk Optimalisasi Air Buangan Turbin PLTMH Garassik di Sungai Garassik Kab. Enrekang - Muhammad Khaidir; Fadhli Rahman; Syahrul Mustafa (Jurnal Mosfet, 2025)
The Garassik Micro-Hydro Power Plant in Panassang Village, Enrekang Regency, with an installed capacity of 3.7 kW, experiences an energy deficit due to the community's electricity demand of 390.74 kWh per day. Despite its efficient operation, the plant generates a maximum of only 88.8 kWh per day, underscoring the need for capacity enhancement. This study explores the potential of utilizing turbine wastewater as an energy source by designing a Multi Powerhouse (MPH) Micro-Hydro Power Plant to optimize water energy usage. The proposed MPH system evaluates water energy potential, determines optimal powerhouse placements for effective head height, and calculates total power output. Unlike the single-powerhouse model, the MPH system addresses water flow limitations, particularly during periods of reduced flow, significantly improving total power output to 160.235 kW, a 171% increase. Key advantages of the MPH model include better utilization of turbine wastewater, enhanced operational flexibility, and improved water energy efficiency. Using a descriptive quantitative research method, this study begins with a location survey to collect turbine wastewater characteristics, followed by mathematical modeling for analysis. Results reveal output flow rates of 0.189 m³/s, 0.187 m³/s, and 0.185 m³/s across three powerhouses, with effective head heights of 24.782 m, 29.725 m, and 34.729 m, respectively. The system uses Crossflow turbines, ideal for medium heads and moderate flow rates. Economic analysis indicates an NPV of IDR 2.400.000.000,- an IRR of 14%, and a BCR of 2.5, with a payback period of 5.45 years, making the project financially viable and sustainable.